2020
DOI: 10.5853/jos.2019.03503
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Visual Aids for Late, Imaging-Guided Endovascular Thrombectomy for Acute Ischemic Stroke

Abstract: Background and Purpose Speedy decision-making is important for optimal outcomes from endovascular thrombectomy (EVT) for acute ischemic stroke (AIS). Figural decision aids facilitate rapid review of treatment benefits and harms, but have not yet been developed for late-presenting patients selected for EVT based on multimodal computed tomography or magnetic resonance imaging.Methods For combined pooled study-level randomized trial (DAWN and DEFUSE 3) data, as well as each trial singly, 100 person-icon arrays (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Most critically ill patients experience disturbance of consciousness, swallowing dysfunction, and metabolic exuberance; therefore, they have higher nutritional needs. However, limited intake leads to high stress response, resulting in malnutrition and reduced immune function[ 10 ]. Western medicine mainly relies on intestinal nutrition support in the aspect of supplemental nutrition; however, it can cause reproduction of pathogenic bacteria and formation of flora disorder, which would eventually lead to excessive activation of systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Most critically ill patients experience disturbance of consciousness, swallowing dysfunction, and metabolic exuberance; therefore, they have higher nutritional needs. However, limited intake leads to high stress response, resulting in malnutrition and reduced immune function[ 10 ]. Western medicine mainly relies on intestinal nutrition support in the aspect of supplemental nutrition; however, it can cause reproduction of pathogenic bacteria and formation of flora disorder, which would eventually lead to excessive activation of systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…65 While caution must be exercised in generalizing from studies of acute stroke patients who did not have cancer, the data indicate that patients treated with thrombectomy for acute proximal MCA occlusion stroke lived the remainder of their lives with fewer neurologic impairments than if untreated and with reduced need for aggressive care and institutionalization following a sentinel cerebrovascular event. 64,66,67,68 While not a factor in this Mr J's case, do-not-intubate (DNI) orders are common and worthy of mention here. DNI orders should not independently influence stroke care decisions "unless otherwise explicitly indicated," as emphasized by an American Heart Association/American Stroke Association statement (Class IIa recommendation).…”
Section: Equity and Evolving Therapiesmentioning
confidence: 94%
“…In one meta-analysis, it was shown that the use of aids such as audiotape recordings or videos was shown to have more of a positive effect in quelling patient worries and increasing overall satisfaction [ 7 ]. Additionally, visual decision aids have been effective in acute mechanical thrombectomy in ischemic stroke patients, allowing for more efficient decision-making and overall better stroke outcomes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%